Debating the good society : a quest to bridge America's moral divide - Schmookler, Andrew Bard (MIT Press, 1999)
"Through the ingenious means of a fictional Internet conversation among two dozen or so Americans from various walks of life and every shade of the ideological spectrum, Debating the Good Society probes two questions lying at the heart of the ongoing culture war in contemporary America: Where does goodness come from, and how is good social order to be achieved?"--BOOK JACKET. "Traditionalists and conservatives, who tend to view human nature as inherently sinful, argue that good order must be imposed from above, by parental authority and ruling powers, by the forces of law and tradition, and, ultimately, by God. Counterculturalists and liberals, who tend to believe in the inherent goodness of human nature, claim that well-supported children will develop into well-ordered adults and that adults empowered to make their own choices will form a healthy, well-ordered society."--BOOK JACKET. "By exposing the limitations of both points of view, Andrew Bard Schmookler shows how the culture war presents a challenge to all Americans. This challenge is to integrate the half-truths advanced by both sides into a higher wisdom, one that promises to take the American experiment - to see whether humans can enjoy both the blessings of liberty and the fruits of good order - to the next level of its evolution, toward which it has been straining for the better part of a century."--Jacket